Nassty Enterprise / Muhammad Naqib Najhan Mohamad Nazri - Muhammad Naqib Najhan, Mohamad Nazri (2020)
Business concepts -simple but limited to show to the customers the little things like our product will change the personalities of the user. Products being offered -cosmetic for men used like face cleanser, hairspray and deodorant Market potential/ Target market -this kind of product is daily used for every people, so I confident that our product will go as far as it can. Competitive advantage -in Malaysia this day, there are not a lot of company are making business in men cosmatic so that will be an advantages for us because low of the competion in it. The profitability -it may give a lot of profit to the company because cosmetic sectors is starting to get a place in the heart Malaysian’s people.